Strategi Pemulihan Pariwisata Pantai Parangtritis Pasca Pandemi Covid-19 Melalui Promosi Kearifan Lokal - Salsabila Hisanah; Fatur Rozak; Lia Warlina (Universitas Komputer Indonesia, 2022)
Parangtritis Beach is one of the famous tourist destinations in Bantul Regency, which has natural beauty and various historical relics and myths or beliefs born from the community that makes people interested in visiting. However, the Covid-19 pandemic has reduced the number of visits and income from the Parangtritis Beach tourism industry. Therefore, this study aims to formulate a tourism recovery strategy after the Covid-19 pandemic in the Parangtritis Coast Region by identifying the potential of local wisdom based on sustainable tourism. The research method used is descriptive qualitative by describing the condition of Parangtritis Beach before and during the pandemic and describing its potential, including the potential of local wisdom of Parangtritis Beach and the formulation of the promotion strategy. The data used in the research were secondary data obtained through related agencies, literature studies, and information from the news. The management of Parangtritis Beach tourism after the Covid-19 pandemic is by promoting local wisdom of Parangtritis Beach, such as traditional ceremonies (Labuhan, Peh Cun, Pisungsung), buildings (Langse Cave), traditions (Parang Wedang Baths, Parangkusumo), arts (padusan, performing arts) and crafts. This strategy requires the role of the community by revitalizing traditional institutions, forming regional arts councils, and increasing the involvement of traditional leaders.This formulated strategy needs to be based on sustainable tourism and follow strict health protocols for tourist safety. Key Words : Covid-19, local wisdom, Parangtritis Beach, sustainable tourism